(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Pneumonia is an infectious disease that often occurs in toddlers and causes high morbidity and mortality rates. An infection of the lower respiratory system known as pneumonia attacks one or two lungs, especially in the alveoli, so that it interferes with their function in the exchange of oxygen and carbon dioxide gases (UNICEF, 2024). To overcome the existing problems, a strategy that involves community service activities, such as providing health education, must be implemented. The implementation of activities starts from the preparation stage, starting from making proposals and permits, and the implementation stage is carried out by carrying out two activities, namely activity 1: Providing health education and demonstrations, and activity 2: evaluating the practice of cadres’ abilities in providing education to the community and classifying pneumonia in toddlers. The media used are interactive, including pocket books, videos on early detection and treatment of toddlers with pneumonia, presentation slides, and props, which will provide increased attention and ease of understanding the material. The evaluation process was also carried out using knowledge questionnaires and observation sheets. This activity was carried out on 10 cadres in the work area of the Kersanegara Health Center which showed an increase in the level of knowledge of cadres There was an increase in knowledge and skills, where the pretest of knowledge with the good category was 30%, while the posttest was 50%, then there was an increase in skills for the pretest by 10%, while the posttest with the good category was 100%. It is hoped that this education can be carried out interestingly, thereby increasing cadre knowledge and efforts to prevent pneumonia.